South Korean Pop Music Idol Portrait Upload on Instagram Under Copyright - Muzakki Ubaydillah; Budi Hermono (NOVUM : JURNAL HUKUM, 2025)
Uploading K-Pop idol portraits on Instagram is the implementation of economic rights over portraits belonging to the subject of the portrait. Fans are not allowed to implement economic rights over portraits to earn profit without permission. The researcher aims to analyze the uploading of K-Pop idol portraits on Instagram based on copyright and the legal consequences that fans can receive. This is normative legal research using a statute and conceptual approach. The research results reveal that fans are also not allowed to upload K-Pop idol portraits on Instagram even without profitable purposes without permission because copyright limits the implementation of economic rights over portraits. Uploading K-pop idol portraits on Instagram can have legal consequences, such as compensation and termination of Lysn services which fans have purchased.